Stakeholder Participation in Waste Management Communication - Dhini Ardianti; Uud Wahyudin; Herlina Agustin; Ute Lies Siti Khadijah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study explores stakeholder participation in waste management communication in Bandung City, which frequently faces waste emergencies. Despite the government's implementation of various waste management programs, the issue remains unresolved. Effective waste management requires active collaboration among all stakeholders, including government agencies, non-governmental organizations, media, and community leaders. Using a constructivist paradigm with a qualitative case study approach, this research examines the roles of government entities (Bandung City Environment Agency, PD. Kebersihan, and Bapelitbang), non-governmental actors (Forum Bandung Juara Bebas Sampah/BJBS, including environmental activists, academics, and business representatives), as well as media and community leaders. Informants were purposively selected based on their involvement in waste management efforts. Findings reveal that collaboration occurs between the government, legislators, and grassroots environmental activist groups, such as BJBS, which directly engages in waste management initiatives. However, from a pentahelix collaboration perspective, effective communication requires greater involvement of mass media, both conventional and digital. Currently, waste management communication relies mainly on social media accounts with limited reach, such as Humas Bandung, Dinas Lingkungan Hidup Kota Bandung, and Forum BJBS. This limited engagement hinders public awareness and participation. To achieve a sustainable solution, public involvement and awareness must be strengthened, ensuring that waste management is a shared responsibility rather than solely the government's duty.